2018
DOI: 10.3389/fonc.2018.00280
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the NLRP3 Inflammasome With Methylene Blue as Treatment Adjunct in Myelodysplasia

Abstract: Myelodysplasia refers to a group of clonal hematopoietic neoplasms characterized by genetic heterogeneity, different clinical behaviors and prognoses. Some of this group of bone marrow failure conditions have known external causes, some are of unknown origin. Within marrow, intracellular, and extracellular elements of the innate immune system are activated and contribute to creation of multiple cytogenetic abnormalities and are central to the mode of hematopoietic cell failure. Basiorka et al. showed that NLRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Methylene blue could reduce hypoxia, one of the main complications in COVID-19 patients, by decreasing methemoglobin. Moreover, methylene blue decreases inflammation and oxidative stress [ 48 , 49 ]. Pro-inflammatory cytokines and nitric oxide were considerably increased in the cytokine storm due to COVID-19 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methylene blue could reduce hypoxia, one of the main complications in COVID-19 patients, by decreasing methemoglobin. Moreover, methylene blue decreases inflammation and oxidative stress [ 48 , 49 ]. Pro-inflammatory cytokines and nitric oxide were considerably increased in the cytokine storm due to COVID-19 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our group is investigating the potential of fluorescence polarization (FP) imaging [14] for cancer detection. Specifically, we focus on FP exhibited by exogenous methylene blue (MB), a phenothiazinium dye approved by the United States Food and Drug Administration for several clinical indications [15,16]. Previously, we demonstrated that MB enhanced contrast of brain neoplasms [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…MB improves mitochondrial function by inducing peroxisome proliferator-activated receptor γ coactivator 1 PGC1α, a central mediator of mitochondrial biogenesis [56], and downregulates the expression of NACHT, Leucine-rich repeat (LRR), and Pyrin (PYD) dominions that contain protein 3 (NLRP3) an inflammasome produced by bone marrow derivatives from macrophages induced by ATP. In addition, MB might regulate inflammation, influencing the signaling way of pro-inflammatory nuclear factor-κB (NF-κB) and inhibiting caspase-1 activation to reduce apoptosis [57].…”
Section: Methylene Bluementioning
confidence: 99%